Studying the multilevel impact of cohesion versus structural holes in knowledge networks on adaptation to IT‐enabled patient‐care practices. (12th April 2019) - Raman, Roopa; Grover, Varun
Abstract: We investigate the impact of cohesion versus structural holes in two different types of knowledge networks—help‐seeking networks and voluntary contribution networks—on adaptation to health IT‐enabled patient‐care practices. In a multimethod study conducted within a large hospital system, qualitative and quantitative data were collected from 806 clinicians working with electronic medical record systems in 27 inpatient patient‐care units. Multilevel analysis of the data revealed that overall network cohesiveness versus location in structural hole positions related to adaptation differently, depending on the type of network. In help‐seeking networks, location in structural hole positions was negatively related to adaptation, while network cohesion had a bell‐shaped curvilinear relationship with adaptation; in voluntary contribution networks, the overall cohesiveness of the network was negatively related to adaptation, but location in structural hole positions was irrelevant to adaptation. Our findings suggest a more nuanced way of monitoring and utilising different sets of informal social interactions at work to maximise employees' adaptation to IT‐enabled work.